The Total Cost of Corporate Borrowing in the Loan Market: Don't Ignore the Fees - BERG, TOBIAS; SAUNDERS, ANTHONY; STEFFEN, SASCHA (Journal of Finance, 2016)
ABSTRACT More than 80% of U.S. syndicated loans contain at least one fee type and contracts typically specify a menu of spreads and fee types. We test the predictions of existing theories on the main purposes of fees and provide supporting evidence that: (1) fees are used to price options embedded in loan contracts such as the drawdown option for credit lines and the cancellation option in term loans, and (2) fees are used to screen borrowers based on the likelihood of exercising these options. We also propose a new total‐cost‐of‐borrowing measure that includes various fees charged by lenders.